2007
DOI: 10.1159/000101697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Haemodialysis on Circulating Endothelial Progenitor Cell Count

Abstract: During haemodialysis (HD) the endothelium is the first organ to sense and to be impaired by mechanical and immunological stimuli. We hypothesized that a single HD session induces mobilization of endothelial progenitor cells (EPCs) and that cardiovascular risk factors may influence this process. We quantified EPCs at different maturational stages (CD34+, CD133+/VEGFR2+) in blood samples from 30 patients, during HD and on the interdialytic day, and in 10 healthy volunteers. Samples were drawn at the start of HD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 78 publications
2
17
0
Order By: Relevance
“…Corroboratory, Sturiale et al (38) and Choi et al (5) have described reduced numbers of CD34 ϩ and CD133 ϩ EPC in patients with CKD that undergo hemodialysis treatment. Commonly, this implies that the production, or mobilization of CD34 ϩ EPC from the bone marrow is impaired in patients with CKD.…”
Section: Discussionmentioning
confidence: 97%
“…Corroboratory, Sturiale et al (38) and Choi et al (5) have described reduced numbers of CD34 ϩ and CD133 ϩ EPC in patients with CKD that undergo hemodialysis treatment. Commonly, this implies that the production, or mobilization of CD34 ϩ EPC from the bone marrow is impaired in patients with CKD.…”
Section: Discussionmentioning
confidence: 97%
“…Cytofluorimetry is considered the gold standard for the quantitative enumeration of EPC: it is sensitive, accurate and reproducible (9). All peripheral blood specimens were collected and stored in 0.34 mol/L K3EDTA anticoagulant, and all processing was completed within 2 h. Peripheral blood progenitor cells were analyzed for the expression of cell surface antigens with direct three-color analysis using fluorescein isothiocyanate (FITC)-conjugated, phycoerythrin (PE)-conjugated, and allophycocyanin (APC)-conjugated monoclonal antibodies (mAbs) by flow cytometry analysis (FACSCalibur; BD, Franklin Lakes, USA), as reported elsewhere (10,11). Briefly, before staining with specific monoclonal antibodies, cells were treated with fetal calf serum for 10 min, after which samples were washed with a buffer containing phosphate-buffered saline and 0.5% bovine albumin.…”
Section: Quantification Of Epcsmentioning
confidence: 99%
“…We performed the CPT, which has often been used in the literature for the diagnosis of cardiovascular reactivity in normotensive and hypertensive subjects (24). Recently we found elevated numbers of EPCs in patients undergoing hemodialysis, reflecting the direct response of bone marrow to hemodynamic stress on vessels (10). Other authors have already demonstrated an increase in stem cells about to undergo endothelial maturation following different pathological vascular stress inductor stimuli (25).…”
Section: Effect Of Cold Pressor Test On Epcsmentioning
confidence: 99%
“…Endothelial integrity is maintained by a balance between injury and repair, a process which is supported by endothelial progenitor cells (EPCs) [3,4]. Endothelial damage can be repaired by the migration and proliferation of endothelial cells that are contiguous with the lesions or by EPCs [5]. Various risk factors for CV events have been associated with reduced numbers of circulating EPCs and impaired EPC function, including proliferation, migration, and survival [6,7].…”
Section: Introductionmentioning
confidence: 99%